2019
DOI: 10.22462/10.12.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy in treatment of sudden sensorineural hearing loss: finding for the maximal therapeutic benefit of different applied pressures

Abstract: We compared the efficacy of hyperbaric oxygen (HBO2) therapy used in the treatment of sudden sensorineural hearing loss (SSNHL) as a supplementary therapy to the first-line medical treatment according to the different applied pressures used in HBO2 treatment while maintaining the same number of sessions, periodicity and exposure times. We evaluated data from 115 patients suffering from SSNHL within seven days of hearing loss: 35 patients received the standard treatment protocol (control group), and 80 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In the groups compared, delaying HBOT more than 10 days from the time of the first SSNHL symptoms was associated with a reduced treatment efficacy at 1500, 3000, and 4000 Hz. This is in line with current scientific evidence [12,20,[23][24][25]. Cavaliere et al demonstrated a complex relationship between the choice of therapeutical strategy for SSNHL and hearing improvement [26].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the groups compared, delaying HBOT more than 10 days from the time of the first SSNHL symptoms was associated with a reduced treatment efficacy at 1500, 3000, and 4000 Hz. This is in line with current scientific evidence [12,20,[23][24][25]. Cavaliere et al demonstrated a complex relationship between the choice of therapeutical strategy for SSNHL and hearing improvement [26].…”
Section: Discussionsupporting
confidence: 83%
“…In the examined group, there were no statistically significant differences in the decrease in hearing threshold stimulus with respect to the total time of compression (1 vs. 2 h). A selective influence of pressure values on hearing threshold stimulus was, however, demonstrated by Krajcovicova et al [20]. Application of 2.0 ATA improved treatment results in the speech frequency spectrum.…”
Section: Introductionmentioning
confidence: 93%
“…In one study, researchers compared the effect of HBOT under different pressures. 32 They found that at low frequencies, high-pressure oxygen therapy and at higher frequencies, low-pressure oxygen therapy produced better results. In our study, we observed that the healing effect of NBOT at high frequencies is better than HBOT especially on the fifth and seventh days.…”
Section: Discussionmentioning
confidence: 97%